Free text databases in an Integrated Academic Information System (IAIMS) at Columbia Presbyterian Medical Center. - Clark, A. S. (American Medical Informatics Association, 1991)
The use of Folio Views, a PC DOS based product for free text databases, is explored in three applications in an Integrated Academic Information System (IAIMS): (1) a telephone directory, (2) a grants and contracts newsletter, and (3) nursing care plans.